L'influence des épreuves standardisées internationales sur l'évolution des dispositifs et des représentations en matière d'évaluation des acquis des élèves - Xavier Roegiers (Université de Provence, 2011)
This article aims to analyze the growing influence of international standardized tests (PISA...) on local certifications. Originally, these international standardized tests aim to compare student performance in the different countries so as to enable countries to enhance the effectiveness of their educational systems. They are not originally planned to certify student achievement. However, their influence is such that, imperceptibly, it extends to the contents of the local assessing students' achievement, and even to the evaluation procedures. Generally speaking, they indirectly contribute to profoundly alter the representation that the people involved have of certification. This article proceeds in five steps. First, we present the origin of such standardized tests, both national and international. Second, we question the idea of quality that is associated with those surveys. Third and fourth, we consecutively analyze the advantages (an analysis of the quality of the educational systems, a basis for their regulation ...) and the limits (an enhancement of competition in education, a loss of identity, a diversion of the social function of school...) of this system. Fifth, we develop the idea of an artificial "standardized evaluation bubble", before addressing the question of the trajectory taken by the education systems today.